1987
DOI: 10.1002/eji.1830171214
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of B cell progenitors in vitro: Generation of surface IgM+ B cells, including Ly‐1 B cells, from Thy‐l asialoGM1+ cells in newborn liver

Abstract: We have established a stromal adherent cell line (ST2) from fetal liver that promotes growth and differentiation of early B lineage cells. Many cells in the "null population" (3-5%) from newborn liver that lack antigens found on mature erythroid, myeloid or lymphoid cells proliferate extensively on this ST2 layer. Further division of this cell fraction on the basis of Thy-1 and asialoGM1 (aGM1) expression discriminates cells that predominantly proliferate from those that differentiate on the ST2 layer. Among f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…As expected, no Dlk1 mRNA was present in neonatal liver of the homozygous Dlk1 Ϫ/Ϫ animals or in paternally transmitted Dlk1 Ϫ/ϩ heterozygous animals. and Fr C [30]. We found that the number of Fr A cells was significantly increased in Dlk1 Ϫ/Ϫ mice compared to controls at 4 weeks of age ( Fig.…”
Section: Characterization Of Dlk1 Gene-targeted Mouse Strainmentioning
confidence: 58%
See 1 more Smart Citation
“…As expected, no Dlk1 mRNA was present in neonatal liver of the homozygous Dlk1 Ϫ/Ϫ animals or in paternally transmitted Dlk1 Ϫ/ϩ heterozygous animals. and Fr C [30]. We found that the number of Fr A cells was significantly increased in Dlk1 Ϫ/Ϫ mice compared to controls at 4 weeks of age ( Fig.…”
Section: Characterization Of Dlk1 Gene-targeted Mouse Strainmentioning
confidence: 58%
“…Formation or proliferation of Fr A cells could be enhanced or transition to Fr B and Fr C could be suppressed. Pro-B cells are capable of differentiation from Fr A to Fr B then to Fr C in vitro using stromal cell cultures [4,30]. We used stromal cell cultures to investigate the influence of dlk on pro-B cell proliferation and differentiation.…”
Section: B Cell Development Changes In Dlk1mentioning
confidence: 99%
“…One million lymph node cells were stained with fluoresceinconjugated rat monoclonal antibody RA3-6B2 (anti-B220) and phycocyanin-conjugated rat monoclonal antibody 30H12 (anti-Thyl.2) or phycocyanin-conjugated anti-B220 plus fluorescein-conjugated rat monoclonal antibody 331.12 (antiIgM) and analyzed by a dual-laser FACS 440 (Becton Dickinson) equipped with an argon ion laser and a dye laser (18). Dead cells were excluded from the analysis by adding propidium iodide.…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were fed twice weekly in culture medium (RPMI-1640 supplemented with 5 x 10 -s M 2-ME, 5% FCS, and penicillin/streptomycin) and kept in a humidified 5% CO2 incubator at 37~ Only wells with no nonadherent cells were used in the experiments. The FLST2 stromal cell line used was also maintained in standard medium and passaged by treatment with trypsin-EDTA (26). All experimental cultures with stromal layer were performed in 24-well plates with I ml culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…3) and cultured for 4 d on the FLST2 fetal liver-derived stromal line (26), which has been shown to support B call differentiation from very early stages of development (3). The pro-B cells found in the adult BM and day 16 fetal liver are at an equivalent stage of differentiation since most of these cells are undergoing D-J rearrangement and are also dependent on stromal contact for growth and differentiation (3,9).…”
Section: The Difference In I-a Expression During Fetal Liver and Adulmentioning
confidence: 99%